1995
DOI: 10.1101/gad.9.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of yeast HAP5: a novel subunit of a heterotrimeric complex required for CCAAT binding.

Abstract: The CCAAT-binding factor is a conserved heteromeric transcription factor that binds to CCAAT box-containing upstream activation sites (UASs) within the promoters of numerous eukaryotic genes. The The transcriptional activation of gene expression is mediated by the binding of distinct regulatory factors to specific cis-acting DNA sequence elements, referred to as enhancers or upstream activation sites (UASs), located within the promoters of eukaryotic genes. Many of these transcription factors are composed of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
244
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(249 citation statements)
references
References 62 publications
(96 reference statements)
4
244
1
Order By: Relevance
“…The CCAAT/enhancer element is a common cis-element in the promoters of many genes (Edwards et al, 1998;Kato, 2005;McNabb et al, 1995;Yazawa & Kamada, 2007). Several studies have demonstrated that the CCAAT/enhancer binding protein sites in the human immunodeficiency virus type 1 (HIV-1) LTR are crucial for HIV-1 replication in monocyte/macrophages and for the ability of IFN-b to inhibit ongoing active HIV replication in these cells (Henderson & Calame, 1997;Henderson et al, 1995Henderson et al, , 1996Ravimohan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The CCAAT/enhancer element is a common cis-element in the promoters of many genes (Edwards et al, 1998;Kato, 2005;McNabb et al, 1995;Yazawa & Kamada, 2007). Several studies have demonstrated that the CCAAT/enhancer binding protein sites in the human immunodeficiency virus type 1 (HIV-1) LTR are crucial for HIV-1 replication in monocyte/macrophages and for the ability of IFN-b to inhibit ongoing active HIV replication in these cells (Henderson & Calame, 1997;Henderson et al, 1995Henderson et al, , 1996Ravimohan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Since HAPC is part of PENR1 and since for the HAP-like mouse CCAAT-binding complex NF-Y it was shown that binding of this heteromeric factor distorted DNA in vitro (Ronchi et al, 1995), we wished to find out whether this is also true for binding of HAP-containing protein complexes in lower eukaryotes. Hence, a DNA fragment spanning the PENR1-binding site derived from the intergenic region of acvA and ipnA was cloned into plasmid pBEND4 to give pBENDIRAI (see Materials and Methods section).…”
Section: Methodsmentioning
confidence: 99%
“…The aat (penDE) gene lies fusions) (Then Bergh et al, 1996);FLIRT∆hapC-1, yA1, biA1; 825 bp downstream of the ipnA gene (Ramon et al, 1987;Montenegro argB2 ::pFLIRT; hapC ::riboB ϩ (this study) ; FLIRT∆hapC-2, et al, 1990 ;Tobin et al, 1990). biA1; argB2 ::pFLIRT; pyroA4 ; hapC::riboB ϩ (this study) ; OLAB1, biA1; bga0; argB2 ::pOLAB1 (aat-lacZ gene fusion integrated in single copy at the chromosomal argB gene locus) omers (e.g. Hahn and Guarente, 1988;Raymondjean et al, (Litzka et al, 1995);OLAB1MUT1, biA1;bga0;argB2::pO-1988;Chen and Kinsey, 1995;McNabb et al, 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The cloning of NF-Y genes from several species including yeast, maize, lamprey, and sea urchin, evidenced highly conserved domains (16 -22). The NF-YA homology domain can be divided into subunit association and DNA-contacting subdomains (20). The N-terminal contains a hydrophobic and Gln-rich activation surface (18).…”
mentioning
confidence: 99%